How to treat the frail elderly: The challenge of multimorbidity and polypharmacy - Tannenbaum, Cara (Canadian Urological Association Journal, 2013)
The pharmacologic management of lower urinary tract symptoms in frail older adults is complicated by two key considerations: the increased likelihood of comorbidities and the increased likelihood of polypharmacy. This brief review summarizes how these factors may impact treatment choices in this population.